The effect of process-genre writing approach on students’ essay at a college in Kwara State, Nigeria - Ajoke, Alabere Rabiat (2018)
The poor performance of university students in the English language particularly in essay calls for the review of the approach to teaching writing. This research focuses on the effects of Process-Genre Approach on students' essay in English as a second language context at a College in Nigeria. This study used the quasi-experimental design involving a pre-test and post-test. The intervention took six weeks to examine the effectiveness of the Process Genre Approach in enhancing writing skills in terms of content, organization, expression, and mechanics. The materials used for the intervention were the English for tertiary Institutions textbook and the essay questions for the pre and post tests were taken from the West Africa Examination Council (WAEC). 80 undergraduate degree students and two English language teachers at the college participated in the study. The data were analyzed using analysis of covariance (ANCOVA) to test for statistically significant difference between the experimental group taught with Process-Genre Approach and the control group taught with the Product Approach. The findings indicated that no statistically significant difference between the pre-test scores of the control and the experimental groups showing homogeneity in their performance and language abilities prior to the interventions. The findings also indicated no difference between the pre-test and post-test scores of the participants in the control group compared to the experimental group with a remarkable difference in the pre-test and post-test scores. These suggested that the Process-Genre Approach to writing in several drafts, considering the context and reader had effects on the students' performance in an essay in the content, organization, expression, and mechanics with overall mean scores of 38.62 to 17.99 for Product Approach group. The implementation of the Process-Genre Approach to teaching essay has a positive impact on social change and improvement in writing.